Exposure to zebularine and 5-azaC triggers microsatellite instability in the exposed Arabidopsis thaliana plants and their progeny. (January 2018) - Yao, Youli; Kovalchuk, Igor
Abstract: Plant genome stability can be altered by exposure to stress. Many stresses that are not directly mutagenic can alter genome stability. Our recent work showed that stresses such as salt, heat and drought can change the frequency of homologous recombination. We showed that exposure to stress triggers changes in methylation, and that these changes are important for the establishment of transgenerational response to stress. Here, we tested whether exposure to zebularine or 5-azaC, two chemicals interfering with normal cytosine methylation patterns, would destabilize the genome and lead to transgenerational changes. Exposure to both chemicals resulted in a dose-dependent decrease in global DNA methylation, with changes at symmetrical CNG cytosines being the most pronounced. The analysis of genome instability showed a dose-dependent increase in microsatellite instability and to a lesser degree in recombination frequency in somatic cells of exposed plants. The analysis of the progeny showed that the spontaneous non-induced recombination frequency was decreased in response to zebularine and did not change in response to 5-azaC, whereas the frequency of microsatellite instability increased profoundly in response to both chemicals. At the same time, the analysis of cytosine methylation in progeny of plants exposed to zebularine and 5-azaC showed a more pronounced decrease at CNG cytosines. Our work shows that the maintenance of DNA methylation is likely important for the prevention of microsatellite instability and that hypomethylation may affect genome stability in progeny differently in different genomic regions with genomic regions containing microsatellites being more prone to destabilization. Highlights: DNA methylation may regulate the genome stability. Demethylating agents zebularine or 5-azaC increase microsatellite instability in plants. Microsatellite instability is heritable in response to zebularine and 5-azaC.